Using a graph to schematize the test results of mining dump trucks - Dianov V.A.; Bokarev A.I.; Kartashov A.B.; Dubinkin D.M.; Pashkov D.A. (Горное оборудование и электромеханика, 2025)
The practice of designing newly developed dump trucks, as well as machines in general, is based on and correlates with real operating conditions. Data on real operating conditions are widely used. However, the general problem is the practical complexity of processing large amounts of data for subsequent use in the design process. Many researchers have described the relationship between road surfaces, dynamic loads and the durability of quarry dump truck units. This article proposes a demonstration of a method for processing a large amount of test data to be able to use the obtained result in product development systems, for example, for the potential development of a calculated-experimental method for predicting the resource of components of the supporting system. This work is devoted to finding a method for the best presentation, processing and averaging of the performance indicators of quarry dump trucks that have been tested for a long time. At the moment, there is no single algorithm for processing and using test results, so the authors of the article decided to offer their own method for schematizing test results, which can later be used to solve both general and specific problems. The use of graph schematization allows you to supplement the graph with new types of information or group them in different ways depending on the problem being solved. Previously, telemetry data was considered separately, but now it is possible to supplement the graph with the number of passes along a particular graph edge based on telemetry data. Also, you can consider not individual edges, but their sequence - the route of movement. Thus, in addition to test data, the graph also contains information on the number of passes along roads over a longer period of time, and this data can be supplemented as new information comes in. The main goal of the study is to develop an effective method for processing data obtained during tests of quarry dump trucks. This approach will not only improve the understanding of the nature of the loads, but also optimize the operation and maintenance processes of this equipment.